Effects of Crosswind on Pantograph–Catenary Wear Using Nonlinear Multibody System Dynamic Algorithms - Siripong Daocharoenporn; Mongkol Mongkolwongrojn (Research Square, 2023)
Abstract In this study, a multibody system (MBS) computational framework is developed to determine the exact location of the contact point and wear prediction resulting from the pantograph–catenary interaction. The railroad vehicle models in the MBS computational framework comprise rigid-body railroad vehicles, rigid-body pantograph systems, and flexible catenary systems. To avoid the incremental rotation and cosimulation processes, the nonlinear finite element absolute nodal coordinate formulation is used to model a flexible catenary system in the MBS computational framework and to integrate the rigid-body railroad vehicle and the pantograph and flexible catenary systems into the MBS algorithms. The pantograph–catenary interaction is modeled using an elastic contact formulation developed to include the effect of pantograph–catenary separation and sliding contact. The proposed MBS approach evaluates the location of the contact point, contact force, and normal wear rate (NWR) from the mechanical and electrical contributions. In particular, this investigation considers the vibration caused by a crosswind scenario, the numerical result in the case of a steady crosswind scenario, which contains the advantage of the pantograph–catenary aerodynamic design, and the vibration of the catenary system remains significant after the excitation of steady crosswind. In the case of a steady crosswind, the higher value of the steady crosswind effect significantly increases the mean contact force and NWR from the mechanical contribution. After crosswind load disturbances, the mean contact force decreases, but the standard deviation of the contact force increases. Therefore, the NWR from the electrical contribution increases significantly. However, the total NWR increases with the crosswind velocity.
Keywords: Railway Engineering and Dynamics; Vibration and Dynamic Analysis; Mechanical stress and fatigue analysis